Polyvinyl acetal resin, method for producing polyvinyl acetal resin solution

The polyvinyl acetal resin addresses the issues of foreign matter and mechanical weakness in ceramic green sheets by controlling particle sizes and molecular weights, resulting in improved reliability and electrical performance of multilayer ceramic capacitors.

JP7612928B1Active Publication Date: 2025-01-14SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024092102
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-01-14
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

Conventional polyvinyl acetal resins used in ceramic green sheets for multilayer ceramic capacitors suffer from foreign matter causing short-circuit failures and insufficient mechanical strength, especially in thinner layers, which compromises the reliability and electrical characteristics of the capacitors.

Method used

A polyvinyl acetal resin is developed with controlled particle sizes and ratios in ethanol-toluene solutions, adjusted molecular weights, and specific IR absorption spectrum characteristics to minimize foreign matter and enhance mechanical strength, ensuring smoother ceramic green sheets and improved reliability.

Benefits of technology

The solution results in ceramic green sheets with reduced foreign matter and higher mechanical strength, leading to the production of highly reliable multilayer ceramic capacitors with enhanced electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612928000003
    Figure 0007612928000003
  • Figure 0007612928000001
    Figure 0007612928000001
  • Figure 0007612928000002
    Figure 0007612928000002
Patent Text Reader

Abstract

The present invention provides a polyvinyl acetal resin capable of producing a ceramic green sheet having a high mechanical strength and having a low level of foreign matter in the resin, and capable of producing a multilayer ceramic capacitor having excellent reliability, a method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin, a slurry for ceramic green sheets, a ceramic green sheet, and a multilayer ceramic capacitor. [Solution] When the number of particles with a size of 0.5 to 1.0 μm in a 0.2 mass% ethanol-toluene (ethanol:toluene = 50:50) mixed solution is P(MIX), and the number of particles with a size of 0.5 to 1.0 μm in a 0.2 mass% ethanol solution is P(EOH), P(MIX) is 1 to 20,000 particles / 10 ml, and P(EOH) / P(MIX) is 1.2 to 7.0, and in an IR absorption spectrum measured by an infrared spectrophotometer, the wavenumber is 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers showing the transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1 A polyvinyl acetal resin having a hydroxyl group amount converted wavenumber width of 8.31 or more, which is calculated using the amount of hydroxyl groups measured by H-NMR and calculated using formula (1). Hydroxyl group amount conversion wave number width (cm -1 / mol%)=[(BA) / hydroxyl group amount] (1)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyvinyl acetal resin, a method for producing a polyvinyl acetal resin solution, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor. [Background technology]

[0002] 2. Description of the Related Art In recent years, electronic components mounted in various electronic devices have become smaller and more laminated, and laminated electronic components such as multilayer circuit boards, laminated coils, and laminated ceramic capacitors are widely used. Among them, multilayer ceramic capacitors are generally manufactured through the following steps. First, a plasticizer, a dispersant, etc. are added to a solution in which a binder resin such as polyvinyl butyral resin or poly(meth)acrylic acid ester resin is dissolved in an organic solvent, and then a ceramic raw material powder is added and mixed uniformly with a mixing device such as a bead mill or a ball mill to obtain a ceramic slurry composition having a certain viscosity after defoaming. This slurry composition is cast onto a support surface such as a release-treated polyethylene terephthalate film or a SUS plate using a doctor blade, reverse roll coater, etc., and the volatile matter such as the solvent is distilled off by heating, etc., and then peeled off from the support to obtain a ceramic green sheet. Next, a conductive paste that will become the internal electrodes is applied to the obtained ceramic green sheets by screen printing, and multiple sheets are alternately stacked and heated and pressed to produce a laminate. After that, a process to thermally decompose and remove the binder resin components and the like contained in the laminate, that is, a so-called degreasing process, is performed, and external electrodes are sintered onto the end faces of the ceramic sintered body obtained by firing to obtain a multilayer ceramic capacitor.

[0003] For example, Patent Document 1 describes a polyvinyl acetal resin suitable as a ceramic binder, which has a specified degree of polymerization, vinyl ester unit content, and degree of acetalization, and in which the molar ratio of the portion acetalized with acetaldehyde to the portion acetalized with butylaldehyde is within a specified range. Furthermore, Patent Document 2 describes a polyvinyl acetal resin having a specific degree of polymerization, a content of vinyl ester units, and a degree of acetalization, and having specific structural units. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-236304 A [Patent Document 2] International Publication No. 2012 / 023517 Summary of the Invention [Problem to be solved by the invention]

[0005] Meanwhile, in recent years, with the trend toward greater functionality and smaller size of electronic devices, multilayer ceramic capacitors are being demanded to have larger capacitance and smaller size, and ceramic green sheets are being demanded to be even thinner. However, when conventional polyvinyl acetal resins are used in thin ceramic green sheets, the presence of foreign matter in the resin can cause short circuits in the multilayer ceramic capacitor and can degrade various electrical properties. Another problem is that the strength of the resulting ceramic green sheets is insufficient.

[0006] The present invention aims to provide a polyvinyl acetal resin that can produce a ceramic green sheet having a small amount of foreign matter in the resin and high mechanical strength, and that can produce a multilayer ceramic capacitor with excellent reliability; a method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor. [Means for solving the problem]

[0007] In the present disclosure 1, when the number of particles of 0.5 to 1.0 μm size in a 0.2 mass% ethanol-toluene (ethanol:toluene=50:50) mixed solution is P(MIX), and the number of particles of 0.5 to 1.0 μm size in a 0.2 mass% ethanol solution is P(EOH), P(MIX) is 1 to 20,000 particles / 10 ml, and P(EOH) / P(MIX) is 1.2 to 7.0, and in an IR absorption spectrum measured by an infrared spectrophotometer, the number of particles of 0.5 to 1.0 μm size is 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers showing the transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1 The polyvinyl acetal resin has a hydroxyl group amount converted wavenumber width of 8.31 or more, which is calculated using the amount of hydroxyl groups measured by H-NMR and is calculated using formula (1). Hydroxyl group amount conversion wave number width (cm -1 / mol%)=[(BA) / hydroxyl group amount] (1) Disclosure 2 is the polyvinyl acetal resin according to Disclosure 1, in which P(EOH) is 4,000 to 60,000 particles / 10 ml. The present disclosure 3 is the polyvinyl acetal resin according to the present disclosure 1 or 2, which has a wavenumber width calculated by the formula (1) of 8.45 or more. The present disclosure 4 is a polyvinyl acetal resin according to any one of the present disclosures 1 to 3, in which Mz(THF) / Mz(NMP) is 1.7 to 2.0, where Mz(THF) is the z-average molecular weight obtained using THF as a mobile phase and Mz(NMP) is the z-average molecular weight obtained using NMP as a mobile phase in a GPC measurement using a differential refractive index detector. The present disclosure 5 is a method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin described in any one of the present disclosures 1 to 4, the method comprising the steps of dissolving the polyvinyl acetal resin in an ethanol / toluene mixed solvent having an ethanol content of 70% by weight or more, removing particles by a filtration step, and then adding toluene. The present disclosure 6 is a slurry for a ceramic green sheet, comprising the polyvinyl acetal resin according to any one of the present disclosures 1 to 4, an organic solvent, and ceramic powder. The seventh aspect of the present disclosure is a ceramic green sheet obtained by using the slurry for the ceramic green sheet according to the sixth aspect of the present disclosure. The eighth aspect of the present disclosure is a multilayer ceramic capacitor obtained by using the ceramic green sheet according to the seventh aspect of the present disclosure. The present invention will be described in detail below.

[0008] As a result of intensive research, the present inventors have found that the number of particles having a size of 0.5 to 1.0 μm in an ethanol solution is within a predetermined range relative to the number of particles having a size of 0.5 to 1.0 μm in an ethanol-toluene mixed solution, and that the number of particles having a size of 0.5 to 1.0 μm in an ethanol solution is within a predetermined range, and that the number of particles having a size of 0.5 to 1.0 μm in an IR absorption spectrum measured by an infrared spectrophotometer is within a range of 3050 to 3750 cm -1 The inventors have found that a polyvinyl acetal resin having a peak wavenumber width within a predetermined range has less foreign matter in the resin, can give a ceramic green sheet with high mechanical strength, and can fabricate a multilayer ceramic capacitor with excellent reliability, and have completed the present invention.

[0009] In the polyvinyl acetal resin of the present invention, P(EOH) / P(MIX) is 1.2 to 7.0, where P(MIX) is the number of particles having a size of 0.5 to 1.0 μm in a 0.2 mass% ethanol-toluene (ethanol:toluene=50:50) mixed solution, and P(EOH) is the number of particles having a size of 0.5 to 1.0 μm in a 0.2 mass% ethanol solution. The number of particles of 0.5 to 1.0 μm size is measured by preparing a given solution (0.2 mass % ethanol-toluene mixed solution, 0.2 mass % ethanol solution) and then measuring the number of particles of 0.5 to 1.0 μm diameter using a particle counter. When the P(EOH) / P(MIX) is within the above range, the uniformity of the slurry is improved, a smoother ceramic green sheet can be produced, and sheet defects such as cracks are less likely to occur, which is advantageous in that the reliability of the obtained multilayer ceramic capacitor is improved. The above P(EOH) / P(MIX) is preferably 3.3 or more, more preferably 4.3 or more, and preferably 6.5 or less, more preferably 6.5 or less. In the present invention, P(EOH) / P(MIX) is an index of the ease of particle deposition in ethanol. As the particle counter, for example, "KS-42C" manufactured by Rion Co., Ltd. can be used. For example, particle measurement using the above particle counter is preferably carried out in a clean room at 23°C.

[0010] The polyvinyl acetal resin of the present invention has a particle number P(EOH) of 0.5 to 1.0 μm in a 0.2 mass% ethanol solution of 4000 to 60000 particles / 10 ml, and more preferably 5000 particles / 10 ml or more and 50000 particles / 10 ml or less. By setting it within the above range, particles in the resin solution can be efficiently removed. The above P(EOH) is more preferably 7000 particles / 10 ml or more, and more preferably 40000 particles / 10 ml or less.

[0011] The polyvinyl acetal resin of the present invention has a particle number P(MIX) of 0.5 to 1.0 μm in a 0.2 mass% ethanol-toluene (ethanol:toluene=50:50) mixed solution of 1 to 20,000 particles / 10 ml. The above P(MIX) is preferably 10 particles / 10 ml or more and 15,000 particles / 10 ml or less. By setting it within the above range, particles in the resin solution can be efficiently removed. The above P(MIX) is more preferably 100 particles / 10 ml or more, and more preferably 8,000 particles / 10 ml or less.

[0012] The above P(EOH) / P(MIX), P(EOH), and P(MIX) can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, the amount of hydroxyl groups, the amount of acetyl groups, and the like of the polyvinyl acetal resin. In particular, the above P(EOH) / P(MIX) can be adjusted by changing the hydrolysis temperature, hydrolysis time, aldehyde introduction temperature, temperature rise time, reaction temperature, reaction time, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular, it can be adjusted by changing the hydrolysis temperature, hydrolysis time, holding (aging) temperature, and holding (aging) time.

[0013] The polyvinyl acetal resin of the present invention has an IR absorption spectrum measured by an infrared spectrophotometer having a wave number of 3050 to 3750 cm -1When the minimum transmittance of the peak within the range is X (%), and among the wavenumbers exhibiting a transmittance a (%) that satisfies [100-(100-X) / 2], the wavenumber width calculated as the amount of hydroxyl groups calculated by the above formula (1) is 8.31 or more. By setting the thickness within the above range, it is possible to obtain a ceramic green sheet having even higher mechanical strength. The lower limit of the hydroxyl group amount converted wave number width is preferably 8.45, more preferably 8.70, and even more preferably 8.84, while the upper limit is preferably 10.00, and more preferably 9.70. In the present invention, the hydroxyl group amount converted wavenumber width is an index that the positions of hydroxyl groups are continuous. The IR absorption spectrum can be measured by a transmission method using a Fourier transform infrared spectrophotometer (such as HORIBA's "FT-720" or JASCO's "FT / IR-4000") at 20°C.

[0014] The polyvinyl acetal resin of the present invention is 1 The wavenumber width of the hydroxyl group-acetyl group amount calculated by the following formula (2) using the amounts of hydroxyl groups and acetyl groups measured by 1 H-NMR is preferably 6.5 to 18.0. Hydroxyl group-acetyl group amount converted wavenumber width = [(BA) / hydroxyl group amount / acetyl group amount] (2) By setting the thickness within the above range, a ceramic green sheet having high mechanical strength can be obtained. The lower limit of the hydroxyl group-acetyl group converted wave number width is more preferably 10.5, and even more preferably 11.0, and the upper limit thereof is more preferably 16.0, and even more preferably 14.0.

[0015] In the analysis of polyvinyl acetal resin using the above infrared spectrophotometer, the spectrum originating from the stretching vibration of the CH bond of polyvinyl acetal resin was observed at 2980 cm -1 The above peak analysis shows that the minimum transmittance of the peak due to the stretching vibration of the C-H bond is around 2500 cm -1 and 3050cm-1 The film thickness of the measurement sample is adjusted so that the film thickness is 20 to 25% of the baseline obtained by connecting the line and the line. Furthermore, the measurement results are -1 A baseline is drawn for peaks that appear within this range, and the data is corrected so that the transmittance at both ends of the peak is 100%.

[0016] The hydroxyl group amount converted wavenumber width can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, the amount of hydroxyl groups, the amount of acetyl groups, etc. of the polyvinyl acetal resin. In particular, the wavenumber width can be adjusted by changing the hydrolysis temperature, hydrolysis time, aldehyde introduction temperature, temperature rise time, reaction temperature, reaction time, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular, it can be adjusted by changing the temperature rise rate, holding (aging) temperature, and holding (aging) time.

[0017] An example of an IR absorption spectrum of the polyvinyl acetal resin of the present invention measured by an infrared spectrophotometer at 20° C. is shown in Fig. 1. In Fig. 1, the vertical axis represents transmittance and the horizontal axis represents wave number. In the IR absorption spectrum shown in FIG. 1, the minimum transmittance X is 65.7%. The transmittance a (%) that satisfies [100-(100-X) / 2] is 82.85%, and the wave number A on the low wave number side is 3297 cm -1 , the wave number B on the high wave number side is 3557 cm -1 It is. In the above case, if the amount of hydroxyl groups is 30 mol%, the hydroxyl group amount converted wavenumber width [(BA) / amount of hydroxyl groups] is 8.67 (cm -1 / mol%). The wave number A is 3250 cm -1 More than 3270cm is preferable. -1 More than 3350 cm is more preferable. -1 The following is preferable: 3330cm -1 The following is more preferred: The wave number B is 3530 cm-1 More than 3550cm is preferable. -1 More preferably, 3600 cm -1 The following is preferable: 3580cm -1 The following is more preferred: The transmittance a is preferably 80% or more and 85% or less.

[0018] In the polyvinyl acetal resin of the present invention, when the z-average molecular weight obtained in GPC measurement using a differential refractive index detector is Mz(THF) and the z-average molecular weight obtained in the mobile phase using THF is Mz(NMP), the z-average molecular weight obtained in the mobile phase using NMP is Mz(NMP) and the Mz(THF) / Mz(NMP) is preferably 1.7 to 2.0. By keeping the ratio within the above range, a ceramic green sheet having high mechanical strength can be obtained. The above Mz(THF) / Mz(NMP) is preferably 1.75 or more, more preferably 1.80 or more, and the above Mz(THF) / Mz(NMP) is preferably 1.95 or less, more preferably 1.90 or less. In the present invention, Mz(THF) / Mz(NMP) is an index of the intermolecular interaction of the polyvinyl acetal resin. The above Mz(THF) / Mz(NMP) can be calculated by measuring Mz(THF) obtained by using tetrahydrofuran as the mobile phase and solvent and a refractive index detector as the detector, measuring Mz(THF) obtained by using THF as the mobile phase by gel permeation chromatography (GPC) measurement, and then measuring Mz(NMP) obtained by using NMP as the mobile phase by GPC measurement, using N-methylpyrrolidone as the mobile phase and solvent and a refractive index detector as the detector, and calculating Mz(THF) / Mz(NMP).

[0019] The above Mz(THF) is preferably 400,000 or more, more preferably 700,000 or more, and is preferably 6,000,000 or less, more preferably 2,000,000 or less. The above Mz(NMP) is preferably 200,000 or more, more preferably 400,000 or more, and is preferably 4,200,000 or less, more preferably 1,200,000 or less.

[0020] The above Mz(THF) / Mz(NMP) can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin. In particular, the above Mz(THF) / Mz(NMP) can be adjusted by changing the aldehyde introduction temperature, number of introductions, introduction interval, temperature rise time, reaction temperature, reaction time, holding (aging) temperature, and holding (aging) time during the acetalization reaction described below, and in particular, it can be adjusted by changing the aldehyde introduction temperature, reaction time, temperature rise rate, holding (aging) temperature, and holding (aging) time.

[0021] The polyvinyl acetal resin of the present invention preferably has a solution viscosity of 30 mPa s or more and 600 mPa s or less, when a 5% by mass solution of the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C. In order to improve the tensile strength, the viscosity is more preferably 50 mPa s or more, and even more preferably 65 mPa s or more. In order to improve the viscosity stability of the ceramic slurry composition, the viscosity is more preferably 400 mPa s or less, and even more preferably 200 mPa s or less. The above-mentioned B-type viscometer may be, for example, a TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. In addition, the rotor and rotation speed during viscosity measurement are preferably adjusted appropriately depending on the solution viscosity, and for example, it is preferable to measure using SPINDLE No. M1 to M4 at a rotation speed in the range of 0.3 to 100 rpm.

[0022] The viscosity can be adjusted, for example, by changing the average degree of polymerization and degree of saponification of the raw material polyvinyl alcohol resin, and the temperature and time conditions of the acetalization reaction, and by appropriately setting the amount of acetal groups, hydroxyl groups, acetyl groups, etc. of the polyvinyl acetal resin.

[0023] The polyvinyl acetal resin of the present invention preferably has a structural unit having an acetal group represented by the following formula (3), a structural unit having a hydroxyl group represented by the following formula (4), and a structural unit having an acetyl group represented by the following formula (5).

[0024] [ka]

[0025] In the above formula (3), R 1 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.

[0026] In the above formula (3), R 1 When is an alkyl group having 1 to 20 carbon atoms, examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, a 2-ethylhexyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, an octadecyl group, etc. Among these, a methyl group and an n-propyl group are preferable.

[0027] In the polyvinyl acetal resin of the present invention, the content of the structural unit having the acetal group represented by the above formula (3) (hereinafter also referred to as the "acetal group amount") is preferably 50 mol % in lower limit and 83 mol % in upper limit. When the amount of acetal groups is 50 mol % or more, the solubility in organic solvents can be improved, and when the amount of acetal groups is 83 mol % or less, the polyvinyl acetal resin can have excellent tensile strength. The acetal group amount is more preferably 55 mol % in lower limit and 80 mol % in upper limit, that is, the acetal group amount is preferably 50 to 83 mol %, and more preferably 55 to 80 mol %. The amount of acetal groups is, for example, 1 It can be measured by H-NMR. Regarding the method for calculating the amount of acetal groups, since the acetal groups of polyvinyl acetal resin are obtained by acetalizing two hydroxyl groups of polyvinyl alcohol, the method of counting the two acetalized hydroxyl groups is used.

[0028] In the polyvinyl acetal resin of the present invention, the content of the structural unit having a hydroxyl group represented by the above general formula (4) (hereinafter also referred to as the "hydroxyl group amount") is preferably 18 mol % in lower limit and 40 mol % in upper limit. When the amount of hydroxyl groups is 18 mol % or more, the polyvinyl acetal resin can have high toughness, and when the amount of hydroxyl groups is 40 mol % or less, the solubility in organic solvents can be sufficiently improved. The lower limit of the hydroxyl group amount is more preferably 22 mol % and the upper limit is more preferably 38 mol %. That is, the hydroxyl group amount is preferably 18 to 40 mol %, and more preferably 22 to 38 mol %. By setting the hydroxyl group amount within the above range, the hydroxyl group amount converted wave number width and the hydroxyl group amount converted wave number width of the acetyl group amount can be set within a predetermined range. The amount of hydroxyl groups is, for example, 1 It can be measured by H-NMR.

[0029] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetyl group represented by the above general formula (5) (hereinafter also referred to as the "acetyl group amount") is preferably 0.1 mol % in lower limit and 22.0 mol % in upper limit. When the amount of acetyl groups is 0.1 mol% or more, the increase in viscosity of the slurry composition for ceramic green sheets due to intramolecular and intermolecular hydrogen bonds of hydroxyl groups in the polyvinyl acetal resin can be suppressed.When the amount of acetyl groups is 22.0 mol% or less, the flexibility of the polyvinyl acetal resin is not excessively increased, and the handleability can be improved. The lower limit of the acetyl group amount is more preferably 0.5 mol % and the upper limit is more preferably 15.0 mol %. That is, the acetyl group amount is preferably 0.1 to 22.0 mol %, and more preferably 0.5 to 15.0 mol %. By setting the amount of acetyl groups within the above range, the wave number width of the hydroxyl group amount converted into the amount of acetyl groups can be set within a predetermined range. The amount of acetyl groups is, for example, 1 It can be measured by H-NMR.

[0030] In the polyvinyl acetal resin of the present invention, from the viewpoint of maintaining mechanical strength when a thin film ceramic green sheet is produced, the average polymerization degree has a preferable lower limit of 500, more preferably 600, and from the viewpoint of solubility in organic solvents and dissolution viscosity, the average polymerization degree is preferably 10,000, more preferably 5,000. That is, the average polymerization degree is preferably 500 to 10,000, more preferably 600 to 5,000. The average degree of polymerization of the polyvinyl acetal resin is the same as that of the raw material polyvinyl alcohol, and can be measured in accordance with JIS K 6726.

[0031] The polyvinyl acetal resin of the present invention can usually be produced by acetalizing a polyvinyl alcohol resin.

[0032] As the polyvinyl alcohol resin, for example, a conventionally known polyvinyl alcohol resin such as a resin produced by saponifying a polyvinyl acetate resin with an alkali, an acid, aqueous ammonia or the like can be used. The polyvinyl alcohol resin may be fully saponified, but it does not need to be fully saponified as long as there is at least one unit having two consecutive hydroxyl groups at the meso and racemo positions at at least one position in the main chain, and may be a partially saponified polyvinyl alcohol resin. In addition, as the polyvinyl alcohol resin, a copolymer of vinyl alcohol and a monomer copolymerizable with vinyl alcohol, such as an ethylene-vinyl alcohol copolymer resin or a partially saponified ethylene-vinyl alcohol copolymer resin, may also be used. The polyvinyl acetate resin may be, for example, an ethylene-vinyl acetate copolymer.

[0033] The polyvinyl alcohol resin preferably has a degree of saponification of 70 mol % or more. The saponification degree is more preferably 76 mol % or more and 99.4 mol % or less, and even more preferably 78 mol % or more and 99.2 mol % or less. That is, the saponification degree is more preferably 76 to 99.4 mol %, and even more preferably 78 to 99.2 mol %. By using the polyvinyl alcohol resin, the Mz can be set within a predetermined range.

[0034] The above acetalization is preferably carried out in a water solvent, in a mixed solvent of water and an organic solvent compatible with water, or in an organic solvent. As the organic solvent compatible with water, for example, an alcohol-based organic solvent can be used. Examples of the organic solvent include alcohol-based organic solvents, aromatic organic solvents, aliphatic ester-based solvents, ketone-based solvents, lower paraffin-based solvents, ether-based solvents, amide-based solvents, and amine-based solvents. Examples of the alcohol-based organic solvent include methanol, ethanol, n-propanol, isopropanol, n-butanol, and tert-butanol. Examples of the aromatic organic solvent include xylene, toluene, ethylbenzene, and methyl benzoate. Examples of the aliphatic ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, methyl acetoacetate, and ethyl acetoacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methylcyclohexanone, benzophenone, and acetophenone. Examples of the lower paraffin solvent include hexane, pentane, octane, cyclohexane, and decane. Examples of the ether solvent include diethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol diethyl ether. Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetanilide. Examples of the amine solvent include ammonia, trimethylamine, triethylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline, and pyridine. These solvents may be used alone or in combination of two or more. Among these, ethanol, n-propanol, isopropanol, and tetrahydrofuran are particularly preferred from the viewpoints of solubility in the resin and ease of purification.

[0035] The acetalization is preferably carried out in the presence of an acid catalyst. The acid catalyst is not particularly limited, and examples thereof include mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, carboxylic acids such as formic acid, acetic acid, and propionic acid, and sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, and paratoluenesulfonic acid. These acid catalysts may be used alone or in combination of two or more compounds. Among them, hydrochloric acid, nitric acid, and sulfuric acid are preferred, and hydrochloric acid is particularly preferred.

[0036] The aldehyde used in the acetalization reaction may be an aldehyde having a chain aliphatic group, a cyclic aliphatic group, or an aromatic group having 1 to 10 carbon atoms. Any known aldehyde may be used as the aldehyde. The aldehyde used in the acetalization reaction is not particularly limited, and may be, for example, an aliphatic aldehyde, an aromatic aldehyde, or the like. Examples of the aliphatic aldehyde include formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, n-hexylaldehyde, 2-ethylbutyraldehyde, 2-ethylhexylaldehyde, n-heptylaldehyde, n-octylaldehyde, n-nonylaldehyde, n-decylaldehyde, and amylaldehyde. Examples of the aromatic aldehyde include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde. These aldehydes may be used alone or in combination of two or more. Among them, preferred aldehydes are formaldehyde, acetaldehyde, butylaldehyde, 2-ethylhexylaldehyde, and n-nonylaldehyde, which have excellent acetalization reactivity and can provide sufficient internal plasticizing effect to the resin produced, thereby imparting good flexibility. In addition, more preferred are formaldehyde, acetaldehyde, and butylaldehyde, which can provide an adhesive composition that is particularly excellent in impact resistance and adhesion to metals.

[0037] The amount of the aldehyde to be added can be appropriately set according to the amount of acetal groups in the target polyvinyl acetal resin. In particular, it is preferable to add 50 mol% or more and 95 mol% or less, more preferably 55 mol% or more and 90 mol% or less, based on 100 mol% of polyvinyl alcohol, because this allows the acetalization reaction to proceed efficiently and makes it easy to remove unreacted aldehyde.

[0038] In the above acetalization reaction, it is preferable to carry out a hydrolysis step using hydrochloric acid or sodium hydroxide before the acetalization reaction, and it is particularly preferable to carry out a hydrolysis step using hydrochloric acid. By carrying out the above hydrolysis step using hydrochloric acid, P(EOH), P(MIX), and P(EOH) / P(MIX) can be set within a predetermined range. For example, the above hydrolysis step using hydrochloric acid is a step in which polyvinyl alcohol is dissolved in water by heating, hydrochloric acid is added, and the mixture is heated and stirred for a certain period of time to hydrolyze the acetyl groups contained in the polyvinyl alcohol to hydroxyl groups. The temperature (hydrolysis temperature), time (hydrolysis time), and amount of hydrochloric acid in the hydrolysis step may be appropriately adjusted depending on the saponification degree of the raw material polyvinyl alcohol and the target saponification degree after hydrolysis.

[0039] The hydrolysis temperature is preferably 50° C. or higher and 90° C. or lower, more preferably 53° C. or higher and 85° C. or lower, even more preferably 55° C. or higher and 80° C. or lower, and particularly preferably 60° C. or higher and 75° C. or lower. That is, the hydrolysis temperature is preferably 50 to 90° C., more preferably 53 to 85° C., even more preferably 55 to 80° C., and particularly preferably 60 to 75° C. The hydrolysis time is preferably 30 minutes or more and 10 hours or less, more preferably 45 minutes or more and 8 hours or less, even more preferably 1 hour or more and 7 hours or less, and particularly preferably 2 hours or more and 6 hours or less. That is, the hydrolysis time is preferably 30 minutes to 10 hours, more preferably 45 minutes to 8 hours, even more preferably 1 hour to 7 hours, and particularly preferably 2 hours to 6 hours. The amount of hydrochloric acid is preferably 10 parts by weight or more and 250 parts by weight or less relative to 100 parts by weight of polyvinyl alcohol. More preferably, it is 15 parts by weight or more and 200 parts by weight or less, and even more preferably, it is 30 parts by weight or more and 120 parts by weight or less. That is, the amount of hydrochloric acid is preferably 10 to 250 parts by weight, more preferably 15 to 200 parts by weight, and even more preferably 30 to 120 parts by weight relative to 100 parts by weight of polyvinyl alcohol.

[0040] In the acetalization, it is preferable to add the aldehyde at a predetermined temperature, carry out a reaction for a predetermined time (reaction step), and then maintain the reaction at a predetermined temperature (aging step). The temperature at which the aldehyde is introduced is preferably 5°C or higher and 35°C or lower, and more preferably 15°C or higher and 25°C or lower. The time from the addition of the aldehyde to the start of temperature increase (temperature increase start time or reaction time) is preferably 150 minutes or more and 420 minutes or less, and more preferably 180 minutes or more and 360 minutes or less. The temperature rise time is preferably 330 minutes or more and 520 minutes or less, and more preferably 400 minutes or more and 510 minutes or less. Furthermore, when the temperature at the time of adding (charging) the aldehyde is less than 35°C, it is preferable to change the rate of temperature increase from the temperature at the time of adding the aldehyde to 35°C (temperature increase rate 1) and the rate of temperature increase from 35°C to the holding temperature in the aging process (temperature increase rate 2). The above-mentioned temperature rise rate 1 is preferably 0.02° C. / min or more and 0.06° C. / min or less. By setting the temperature rise rate 1 within the above range, the THF viscosity can be set within a predetermined range. The temperature rise rate 2 is preferably 0.10° C. / min or more and 0.30° C. / min or less. By setting the temperature rise rate 2 within the above range, the hydroxyl group amount converted wavenumber width and the hydroxyl group amount / acetyl group amount converted wavenumber width can be set within a predetermined range.

[0041] The retention time in the aging step is preferably 1 hour or more and 5 hours or less, and more preferably 2.5 hours or more and 3 hours or less. The holding temperature in the aging step is preferably 50°C or higher and 70°C or lower, and more preferably 55°C or higher and 65°C or lower. By setting the above-mentioned holding time and holding temperature, the above-mentioned hydroxyl group amount converted wave number width and hydroxyl group amount / acetyl group amount converted wave number width can be set within a predetermined range.

[0042] The present invention also provides a method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin of the present invention, the method comprising the steps of dissolving the polyvinyl acetal resin in an ethanol / toluene mixed solvent having an ethanol content of 70% by weight or more, removing particles by a filtration step, and then adding toluene. By using such a production method, it is possible to produce a polyvinyl acetal resin solution containing even fewer particles. The filtration step may be carried out by filtration using a metal mesh, a ceramic filter, a nonwoven fabric, or a resin filter, or by centrifugation.

[0043] By containing the polyvinyl acetal resin of the present invention and a plasticizer, a resin composition for a ceramic green sheet can be obtained. The resin composition for a ceramic green sheet may contain components such as an antioxidant, a surfactant, an ultraviolet absorber, and an antifoaming agent, so long as the effects of the present invention are not adversely affected.

[0044] As a method for producing the resin composition for ceramic green sheets, for example, a plasticizer and other additives added as necessary are added to a polyvinyl acetal resin obtained by acetalizing a polyvinyl alcohol resin with an aldehyde, and then mixed to obtain a resin composition for ceramic green sheets.

[0045] The resin composition for a ceramic green sheet contains a plasticizer. By adding the plasticizer, the mechanical strength and flexibility of the resulting ceramic green sheet can be significantly improved. Examples of the plasticizer include phthalic acid diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, and alkylene glycol diesters such as triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-heptanoate, and triethylene glycol-di-heptanoate.

[0046] In the resin composition for ceramic green sheets, the content of the plasticizer relative to 100 parts by weight of the polyvinyl acetal resin is preferably 7 parts by weight in lower limit, more preferably 8.5 parts by weight in lower limit, preferably 18 parts by weight in upper limit, more preferably 13.5 parts by weight in upper limit.

[0047] A slurry for ceramic green sheets can be prepared by mixing the polyvinyl acetal resin of the present invention with an organic solvent and ceramic powder.

[0048] The organic solvent is not particularly limited, and may be any solvent capable of dissolving the polyvinyl acetal resin, such as ketones, including acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. Other examples include alcohols, such as methanol, ethanol, isopropanol, and butanol, and aromatic hydrocarbons, such as toluene and xylene. Other examples include esters, such as methyl propionate, ethyl propionate, butyl propionate, methyl butanoate, ethyl butanoate, butyl butanoate, methyl pentanoate, ethyl pentanoate, butyl pentanoate, methyl hexanoate, ethyl hexanoate, butyl hexanoate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate. Other examples include methyl cellosolve, ethyl cellosolve, butyl cellosolve, terpineol, dihydroterpineol, butyl cellosolve acetate, butyl carbitol acetate, terpineol acetate, and dihydroterpineol acetate. In particular, alcohols, ketones, aromatic hydrocarbons and mixed solvents thereof are preferred in terms of coating and drying properties, with a mixed solvent of ethanol and toluene and a mixed solvent of methyl ethyl ketone and toluene being more preferred.

[0049] The content of the organic solvent in the ceramic green sheet slurry is set according to the type of polyvinyl acetal resin used, and is not particularly limited, but if it is too small, it is difficult to exhibit the solubility required for kneading. Also, if it is too large, the viscosity of the ceramic green sheet slurry composition becomes too low, which may cause poor handling when producing a ceramic green sheet. For this reason, the content of the organic solvent is preferably 20% by weight or more and 80% by weight or less.

[0050] The ceramic powder includes powders of oxides or non-oxides of metals or non-metals used in the manufacture of ceramics. The composition of these powders may be a single composition, a compound state, or a mixture. The constituent elements of the metal oxide or non-oxide may be a single element or a plurality of elements, both as cations and anions, and may further include additives added to improve the properties of the oxide or non-oxide. Specific examples of the oxides or non-oxides include oxides, carbides, nitrides, borides, and sulfides of Li, K, Mg, B, Al, Si, Cu, Ca, Sr, Ba, Zn, Cd, Ga, In, Y, lanthanides, actinides, Ti, Zr, Hf, Bi, V, Nb, Ta, W, Mn, Fe, Co, Ni, etc. In addition, specific oxide powders containing multiple metal elements, usually called double oxides, can be classified based on their crystal structure as follows: those with a perovskite structure include NaNbO3, SrZrO3, PbZrO3, SrTiO3, BaZrO3, PbTiO3, BaTiO3, etc.; those with a spinel structure include MgAl2O4, ZnAl2O4, CoAl2O4, NiAl2O4, MgFe2O4, etc.; those with an ilmenite structure include MgTiO3, MnTiO3, FeTiO3, etc.; and those with a garnet structure include GdGa5O4, GdGa5O5, etc. 12 , Y6Fe5O 12 Among these, the modified polyvinyl acetal resin of the present invention exhibits high properties when mixed with BaTiO3 powder in a ceramic green sheet.

[0051] The average particle size of the ceramic powder is not particularly limited, but for example, for producing a thin ceramic green sheet (thickness 5 μm or less), it is preferably 0.5 μm or less.

[0052] The above-mentioned slurry for ceramic green sheets may contain other resins such as polyvinyl acetal resins other than the polyvinyl acetal resin of the present invention, acrylic resins, ethyl cellulose, etc., within the range that does not impair the effects of the present invention. In such a case, the content of the polyvinyl acetal resin of the present invention relative to the total binder resins is preferably 50% by weight or more.

[0053] The above-mentioned slurry for the ceramic green sheet may contain, as necessary, a dispersant, an antioxidant, an ultraviolet absorber, a surfactant, a filler, etc., and in some cases, a small amount of other resin such as an acrylic resin or a urethane resin may be added.

[0054] The method for producing the slurry for the ceramic green sheet is not particularly limited, and examples thereof include a method in which the polyvinyl acetal resin of the present invention, an organic solvent, a ceramic powder, and various additives added as necessary are mixed using various mixers such as a ball mill, a blender mill, and a three-roll mill.

[0055] After the slurry for the ceramic green sheet is applied, the slurry is heated and dried to obtain a ceramic green sheet. The ceramic green sheets can be used to manufacture ceramic electronic components. For example, the ceramic electronic components can be manufactured by carrying out a step of applying a paste for electrode layers to the surfaces of the ceramic green sheets, and a step of stacking the ceramic green sheets on which the electrode layers have been formed, and heat-pressing the stack to obtain a laminate, followed by degreasing and firing the laminate.

[0056] The method for applying the slurry for the ceramic green sheet is not particularly limited, and examples thereof include a method using a roll coater, a die coater, a curtain coater, etc. As for other specific methods, conventionally known methods can be used.

[0057] The ceramic electronic components are not particularly limited, and examples thereof include multilayer ceramic capacitors, multilayer ceramic inductors, capacitors, piezoelectric actuators, multilayer varistors, multilayer thermistors, EMI filters, aluminum nitride multilayer substrates, alumina multilayer substrates, etc. Such multilayer ceramic capacitors also constitute the present invention.

[0058] The method for producing a ceramic electronic component includes a step of applying a paste for electrode layers to the surfaces of the ceramic green sheets. The electrode layer paste can be obtained by dissolving, for example, polyvinyl acetal resin, ethyl cellulose, acrylic resin, etc. as a binder resin in an organic solvent and dispersing conductive powder, etc. These resins may be used alone or in combination of two or more. The electrode layer paste containing polyvinyl acetal resin is preferred because it exhibits excellent adhesion to the ceramic green sheet in the heat-pressing step.

[0059] In the method for producing a ceramic electronic component, the above-mentioned ceramic green sheets having electrode layers formed thereon are produced, and then similarly produced ceramic green sheets having electrode layers formed thereon are stacked and heated and pressed to obtain a laminate, which is then degreased and fired, thereby obtaining a multilayer ceramic electronic component in which problems such as sheet attack and cracks are solved. The above-mentioned heat-pressure bonding step and the steps of degreasing and firing the laminate are not particularly limited, and conventionally known methods can be used. Effect of the Invention

[0060] According to the present invention, it is possible to provide a polyvinyl acetal resin capable of producing a ceramic green sheet having a small amount of foreign matter in the resin and high mechanical strength, and capable of producing a multilayer ceramic capacitor having excellent reliability, as well as a method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor. [Brief description of the drawings]

[0061] [Figure 1] FIG. 2 is a diagram showing an example of an IR absorption spectrum of the polyvinyl acetal resin of the present invention measured by an infrared spectrophotometer at 20° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0063] Example 1 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 3 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the solution. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 2.5 hours to complete the reaction. The mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. The heating time is the time from the start of heating to the time when the temperature is reached.

[0064] (Preparation of ceramic green sheets) [Preparation of resin solution] 8 parts by weight of the obtained polyvinyl acetal resin and 2.1 parts by weight of a plasticizer (G260, manufactured by Sekisui Chemical Co., Ltd.) were added to a mixed solvent of 45 parts by weight of ethanol and 19 parts by weight of toluene, and dissolved with stirring to prepare a solution. Next, the above solution was filtered using a ceramic filter with a pore size of 0.5 μm to obtain a filtered solution. 26 parts by weight of toluene was added to 74.1 parts by weight of the filtered solution and stirred to prepare a resin solution. [Preparation of inorganic powder dispersion] One part by weight of polyvinyl acetal resin (BL-1, manufactured by Sekisui Chemical Co., Ltd.) was added to a mixed solvent of 20 parts by weight of toluene and 20 parts by weight of ethanol, and dissolved by stirring. Next, 100 parts by weight of barium titanate powder (BT01, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained solution, and the mixture was stirred for 180 minutes with a bead mill (Ready Mill, manufactured by Imex Co., Ltd.) to prepare an inorganic powder dispersion. [Preparation of slurry for ceramic green sheets] To 141 parts by weight of the obtained inorganic powder dispersion, 100.1 parts by weight of the resin solution was added, and the mixture was stirred for 90 minutes in a bead mill to obtain a slurry for ceramic green sheets. The obtained slurry was applied onto a release-treated PET film using a coater so that the thickness after drying would be 20 μm, and then the film was dried by heating to prepare a ceramic green sheet.

[0065] Example 2 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 3 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and then heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0066] Example 3 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 3 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 363 minutes), and held at 60°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0067] Example 4 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 2.5 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and then heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0068] Example 5 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 60°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 5.0 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0069] Example 6 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 80°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 1.0 hour. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 3.0 hours to complete the reaction, and neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0070] Example 7 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 60°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 5.0 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 363 minutes), and held at 60°C for 3.5 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0071] Example 8 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 70°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 3.0 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added thereto. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 363 minutes), and held at 60°C for 3.5 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0072] Example 9 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 80°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 1.0 hour. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 363 minutes), and held at 60°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0073] Example 10 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 60°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 5.0 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 180 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.15°C / min (heating time 420 minutes), and held at 60°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0074] Example 11 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 60°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 5.0 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 360 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 3.0 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0075] Example 12 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 88.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 85°C, and 200g of hydrochloric acid with a concentration of 35% by weight was added and held for 0.5 hours. The solution was cooled to 20°C, and 145g of n-butyl aldehyde was added to the mixture. After that, the mixture was heated to 35°C at a heating rate [heating rate 1] of 0.06°C / min after 360 minutes, and heated from 35°C at a heating rate [heating rate 2] of 0.22°C / min (heating time 340 minutes), and held at 55°C for 2.5 hours to complete the reaction. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0076] Comparative Example 1 300 g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%) was added to 3100 g of pure water and dissolved by stirring for about 2 hours at 90° C. The solution was cooled to 40° C., and 200 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butyl aldehyde were added thereto. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0077] Comparative Example 2 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.2 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 20°C, and 200g of hydrochloric acid with a concentration of 35% by weight and 147g of n-butylaldehyde were added to the solution. 30 minutes after the addition, the temperature was increased at a rate of 0.22°C / min (temperature increase time 45 minutes), and the mixture was kept at 40°C for 3 hours to carry out an acetalization reaction. The mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0078] Comparative Example 3 3000g of pure water was added to 260g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve. The solution was cooled to 20°C, and 200g of hydrochloric acid with a concentration of 35% by weight and 147g of n-butyl aldehyde were added to the solution. 60 minutes after the addition, the temperature was raised at a rate of 0.3°C / min (heating time 150 minutes), and the mixture was kept at 60°C for 2.2 hours to carry out an acetalization reaction. The mixture was neutralized, washed with water, and dried by a conventional method to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0079] Comparative Example 4 300 g of polyvinyl alcohol resin (average polymerization degree 1700, saponification degree 98.7 mol%) was added to 3100 g of pure water and dissolved by stirring for about 2 hours at 90° C. The solution was cooled to 40° C., and 200 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butyl aldehyde were added thereto. Thereafter, the mixture was kept at 40° C. for 3 hours to carry out an acetalization reaction, and then neutralized, washed with water and dried in a conventional manner to obtain a white powder of polyvinyl acetal resin. Moreover, in the same manner as in Example 1, ceramic green sheets were produced.

[0080] (evaluation) The polyvinyl acetal resins and ceramic green sheets obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Table 1.

[0081] (1) Evaluation of polyvinyl acetal resin (1-1) Amount of acetal groups, hydroxyl groups, and acetyl groups The polyvinyl acetal resin thus obtained was analyzed using an AV400 spectrometer (manufactured by Bruker Corporation). 1 H-NMR measurement was carried out, and the amounts of acetal groups, hydroxyl groups, and acetyl groups were calculated. The obtained polyvinyl acetal resin was dissolved in DMSO-D6 to a concentration of 1.6% by weight to prepare a measurement solution. 1 H-NMR measurements were carried out at 80 °C.

[0082] (1-2)IR Absorption Spectrum The obtained polyvinyl acetal resin was dissolved in a 1:1 ethanol / toluene mixed solution, and then coated on a PET film. -1 The film thickness of the measurement sample was adjusted so that the minimum transmittance of the peak appearing around the wavelength of 22% was obtained, and a polyvinyl acetal resin sheet was obtained. The IR absorption spectrum of the obtained polyvinyl acetal resin sheet was measured at 20°C using an infrared spectrophotometer (HORIBA, FT-720). The measurement results showed that the IR absorption spectrum of the obtained polyvinyl acetal resin sheet was 0.01 to 0.05 at a wave number of 3050 to 3750 cm. -1 A baseline was drawn for the peaks that appeared within the range, and peak analysis was performed on the data corrected so that the transmittances at both ends of the peak were 100%, and the minimum transmittance X, transmittance a, and peak wavenumbers A and B were measured. 1 The hydroxyl group amount calculated from H-NMR measurement was used to calculate the hydroxyl group amount conversion wavenumber width (cm -1 / mol%)=[(BA) / hydroxyl group amount] was calculated. 1 The amount of acetyl groups determined by H-NMR measurement was used to calculate the wavenumber width of hydroxyl groups converted into the amount of acetyl groups=[(BA) / amount of hydroxyl groups / acetyl groups].

[0083] (1-3) Particles The obtained polyvinyl acetal resin was added to an ethanol-toluene (ethanol:toluene = 50:50) mixed solvent so that the solid concentration of the polyvinyl acetal resin was 0.2 mass%, and the mixture was stirred at 60 rpm using a mix rotor for 24 hours to dissolve the resin, thereby preparing an ethanol-toluene mixed solution. For 10 mL of the resulting ethanol-toluene mixed solution, the number of particles of 0.5 to 1.0 μm size was measured three times using a particle counter (manufactured by RION, KS-42C, KE-40B1), and the average value was taken as D1. Separately, the number of particles in the ethanol-toluene (ethanol:toluene = 50:50) mixed solvent used as the solvent for the ethanol-toluene mixed solution was measured three times using a particle counter (manufactured by RION, KS-42C, KE-40B1), and the average value was taken as C1. From the obtained C1 and D1, P(MIX) was calculated using the following formula. P(MIX)=D1-C1

[0084] Similarly, the obtained polyvinyl acetal resin was added to ethanol so that the solid content concentration of the polyvinyl acetal resin was 0.2 mass%, and the mixture was stirred at 60 rpm using a mix rotor for 24 hours to dissolve the resin, thereby preparing an ethanol solution. For 10 mL of the obtained ethanol solution, the number of particles of 0.5 to 1.0 μm size was measured three times using a particle counter (manufactured by RION, KS-42C, KE-40B1), and the average value was taken as D2. Separately, the number of particles in the ethanol used as the solvent for the ethanol solution was measured three times using a particle counter (manufactured by RION, KS-42C, KE-40B1), and the average value was taken as C2. From the obtained C2 and D2, P(EOH) was calculated using the following formula. In addition, P(EOH) / P(MIX) was calculated from the obtained P(MIX) and P(EOH). P(EOH)=D2-C2

[0085] (1-4) Viscosity measurement The obtained polyvinyl acetal resin was dissolved in a 1:1 mixed solution of ethanol and toluene to a concentration of 5% by mass to prepare a sample for viscosity measurement. The viscosity of the obtained sample for viscosity measurement was measured using a B-type viscometer at a solution temperature of 20°C. The B-type viscometer used was a TVB-10 viscometer (manufactured by Toki Sangyo Co., Ltd.), and the measurements were performed with the following rotation speeds and rotors: Examples 1 to 12 and Comparative Examples 1 to 4: Rotational speed 30 rpm, SPINDLE No. M1

[0086] (1-5)z average molecular weight [Mz(THF), Mz(NMP)] measurement The obtained polyvinyl acetal resin was dissolved in tetrahydrofuran (THF) at a concentration of 0.2% by weight, passed through a PTFE filter with a pore size of 0.45 μm, and measured at a flow rate of 0.35 mL / min using a GPC apparatus HLC-8420 (manufactured by Tosoh Corporation), THF as the mobile phase, a differential refractive index detector Bryce type double pass (manufactured by Tosoh Corporation) as the detector, and a column TSKgelSuperHZM-H (manufactured by Tosoh Corporation). The obtained measurement results were calibrated using a molecular weight calibration curve prepared with a monodisperse polystyrene standard sample to obtain the z-average molecular weight Mz (THF). Similarly, the obtained polyvinyl acetal resin was dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.2% by weight, passed through a PTFE filter with a pore size of 0.45 μm, and measured at a flow rate of 0.5 mL / min using a GPC apparatus GPC-101 (Shodex Co., Ltd.), a mobile phase NMP, a detector RI-715 (Shodex Co., Ltd.), and a column LF-804 (Shodex Co., Ltd.). The obtained measurement results were calibrated using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample to obtain the z-average molecular weight Mz (NMP). From the obtained Mz(THF) and Mz(NMP), "Mz(THF) / Mz(NMP)" was calculated. Then, using the THF viscosity obtained from the above viscosity measurement, "[THF viscosity / Mz(NMP)]×10000" was calculated.

[0087] (2) Evaluation of ceramic green sheets (2-1) Surface roughness The ten-point average roughness (Rz) of the obtained ceramic green sheets was measured in accordance with JIS B 0601 (1994) and evaluated according to the following criteria. AA: Rz is 0.25μm or less A: Rz is greater than 0.25 μm and less than 0.30 μm. B: Rz is 0.30 μm or more and less than 0.40 μm C: Rz is 0.40 μm or more

[0088] (2-2) Breaking stress, breaking strain The obtained ceramic green sheet was cut into a size of 5 cm x 1 cm to prepare a test piece. The test piece was pulled at a tensile speed of 500% / min using a tensile tester (Shimadzu Corporation, AUTOGRAPH AGS-J) and measured at a temperature of 20°C to determine the breaking tensile strength (kg / cm 2 ) was measured. From the obtained values, a stress σ (MPa)-strain ε (%) curve was obtained. Note that 500% / min means a speed at which the test piece is moved a distance five times the distance between the chucks in one minute. The breaking stress and breaking strain were obtained from the obtained stress-strain curve and were evaluated according to the following criteria. (Stress at break) AA:34MPa or more A: 33MPa or more, less than 34MPa B: 30MPa or more, less than 33MPa C: Less than 30MPa (strain at break) AA: 22% or more A: 21% or more, less than 22% B: 17% or more, less than 21% C: Less than 17%

[0089] [Table 1] [Industrial Applicability]

[0090] According to the present invention, it is possible to provide a polyvinyl acetal resin capable of producing a ceramic green sheet having a small amount of foreign matter in the resin and high mechanical strength, and capable of producing a multilayer ceramic capacitor having excellent reliability, as well as a method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin, a slurry for a ceramic green sheet, a ceramic green sheet, and a multilayer ceramic capacitor.

Claims

1. When the number of particles having a size of 0.5 to 1.0 μm in a 0.2 mass% ethanol-toluene (ethanol:toluene=50:50) mixed solution is defined as P(MIX) and the number of particles having a size of 0.5 to 1.0 μm in a 0.2 mass% ethanol solution is defined as P(EOH), P(MIX) is 1 to 20,000 particles / 10 ml and P(EOH) / P(MIX) is 1.2 to 7.0, In the IR absorption spectrum measured by an infrared spectrophotometer, the wave number is 3050 to 3750 cm -1 When the minimum transmittance of the peak within the range is X (%), among the wave numbers exhibiting a transmittance a (%) that satisfies [100-(100-X) / 2], the wave number on the low wave number side is A and the wave number on the high wave number side is B. 1 The polyvinyl acetal resin has a hydroxyl group amount converted wavenumber width of 8.31 or more, calculated by formula (1) using the amount of hydroxyl groups measured by H-NMR, an acetal group amount of 50 mol % or more and 80 mol % or less, and a hydroxyl group amount of 18 mol % or more and 40 mol % or less. Hydroxyl group amount converted wave number width (cm -1 / mol%)=[(B−A) / amount of hydroxyl group] (1)

2. The polyvinyl acetal resin according to claim 1, wherein P(EOH) is 4,000 to 60,000 pieces / 10 ml.

3. The polyvinyl acetal resin according to claim 1 or 2, which has a wavenumber width calculated by the formula (1) of 8.45 or more.

4. 3. The polyvinyl acetal resin according to claim 1, wherein Mz(THF) / Mz(NMP) is 1.7 to 2.0, where Mz(THF) is the z-average molecular weight obtained using THF as a mobile phase and Mz(NMP) is the z-average molecular weight obtained using NMP as a mobile phase in GPC measurement using a differential refractive index detector.

5. A method for producing a polyvinyl acetal resin solution using the polyvinyl acetal resin according to claim 1 or 2, comprising the steps of: a step of dissolving the polyvinyl acetal resin in an ethanol / toluene mixed solvent having an ethanol content of 70% by weight or more, removing particles by a filtration step, and then adding toluene.

6. A slurry for a ceramic green sheet, comprising the polyvinyl acetal resin according to claim 1 or 2, an organic solvent, and ceramic powder.

7. A ceramic green sheet obtained by using the slurry for ceramic green sheet according to claim 6.

8. A multilayer ceramic capacitor obtained by using the ceramic green sheet according to claim 7.

Citation Information

Patent Citations

  • Adhesive composition

    JP1983001766A

  • Polyvinyl acetal resin for ceramic green sheet, slurry composition, ceramic green sheet, and laminate ceramic condenser

    JP2011236304A

  • JPP7432051B

  • Polyvinyl acetal resin, slurry composition prepared therefrom, ceramic green sheet, and multilayer ceramic capacitor

    WO2012023517A1

  • Polyvinyl acetal resin

    WO2021060499A1